(untitled) (Research, Society and Development, 2022)
Introduction: Cleft lip and palate are the most frequently identified congenital malformations in live newborns. Affected individuals usually have numerous changes that affect primary functions, such as motor development, problems with nasal breathing, feeding, hearing, facial growth, tooth development, speech and aesthetics, compromising not only functionality, but also directly impacting the psychological, the quality of life, the family and social nucleus of that individual. Objective: to describe the physiotherapeutic performance in the context of a multidisciplinary team in a rehabilitation center for craniofacial anomalies, focusing on the evaluation and monitoring of the motor development of children with cleft lip and palate. Methodology: This is an experience report of a qualitative nature, related to the work carried out by physiotherapists in a multidisciplinary team, in a reference service in the treatment of craniofacial anomalies, based on care in children aged 0 to 18 months. Results and discussion: The identification of risk factors and knowledge of developmental milestones serve as parameters for the early identification of motor delays, making it possible to carry out an early physical therapy intervention planning. Physiotherapy in craniofacial deformities follows the neuropsychomotor development for early intervention in possible signs of delay, performing evaluation, intervention and guidance to parents or guardians of the child for home stimulation. Conclusion: We conclude that the role of the physical therapist in the treatment of patients with craniofacial anomalies is of paramount importance, intervening as early as possible, always seeking excellence in health and quality of life for patients with craniofacial deformities.